Casinos and Captive Labour Markets: The Case of Casino Windsor - Mazar, Alissa (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2020)
Economically depressed communities across North America have opened casinos based on the promise of creating “good jobs.” Some scholars find that workers benefit from casinos via employment and wage growth, while others find that casinos exploit host communities, including their workers. Yet, little research addresses whom casinos employ and how workers experience the quality of employment. Existing research is based on geographic areas that house multiple casinos where workers have the mobility to move between different casino operators. Across North America, however, casinos are being adopted in economically depressed areas and in limited-licence states with large distances between casinos. Using the case study of Casino Windsor – located in Canada’s economically struggling automotive capital, Windsor, Ontario – this article speaks to whether casinos offer “good jobs” when a single casino exists in an economically struggling area. Based on 48 interviews with Windsor stakeholders and casino workers, media coverage, and descriptive statistics, these findings provide an alternative story of the employment implications of casino development when casino workers are immobile. The immobility of Casino Windsor workers results from a high unemployment rate, the absence of other employment offering comparable remuneration, and an international border. This scenario allows management to rule through disciplinary actions while still reaping the benefits of worker “loyalty” and effort. With states/provinces justifying casino developments to economically devitalized host communities by promising the creation of “good jobs,” researchers and policymakers must consider whether such developments will create and potentially exploit a captive labour supply, leading to the development of not-so-good casino jobs.